GOOD CORPORATE GOVERNANCE, CONSERVATISM ACCOUNTING, REAL EARNINGS MANAGEMENT, AND INFORMATION ASYMMETRY ON SHARE RETURN - Sugiyanto Sugiyanto; Alexander Candra (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
This study aims to analyze the influence of accounting conservatism, real earnings management, and information asymmetry on stock returns. This study uses the sample of all manufacturing companies listed on the Indonesia Stock Exchange during the period 2013 to 2015. The total number of companies used as sample research is 44 companies with observations for three years. Pursuant to purposive sampling method, total of research sample is 132 financial reports and annual reports. The results of this study indicate: (1) Good corporate governance has a significant negative effect on stock return with a significance value of 0.0020.050; (2) Conservatism with accrual-based conservatism proxy has a significant negative effect on stock return with a significance value of 0.032 0.050; (3) Real earnings management with the proxy of discretionary cash flow has no effect on stock return with a significance value of 0.050; and (4) Information asymmetry with proxy of bid-ask spread has no effect on stock return with significance value of 0.453 0.05.